Subclinical Plasmodium spp. Infections in a Community Setting in Bangui, Central African Republic - Nzoumbou-Boko R; Denissio Morissi Nalingbo MCI; Yambiyo BM; Detol R; Moussa ERF; Nalinga D; Namsenei-Dankpea LJVDLG; Manirakiza A; Ayong L; Boum II Y (Research and Reports in Tropical Medicine)
Romaric Nzoumbou-Boko,1,2 Mireille Cornelia Ingrid Denissio Morissi Nalingbo,1,3 Brice Martial Yambiyo,4 Roger Detol,5 Ermeland Rock Feller Moussa,1 Didita Nalinga,1 Lydie Joella-Venus de la Grace Namsenei-Dankpea,4 Alexandre Manirakiza,4 Lawrence Ayong,6 Yap Boum II1,7 1Parasitology Laboratory, Pasteur Institute of Bangui, Bangui, Central Africa Republic; 2Faculty of Science, University of Bangui, Bangui, Central Africa Republic; 3Faculty of Health Sciences, University of Bangui, Bangui, Central Africa Republic; 4Epidemiology Department, Pasteur Institute of Bangui, Bangui, Central Africa Republic; 5Medical Entomology Department, Pasteur Institute of Bangui, Bangui, Central Africa Republic; 6Malaria Research Unit, Centre Pasteur du Cameroun, Yaoundé, Cameroon; 7Faculty of Medicine and Biomedical Sciences, University of Yaoundé I, Yaoundé, CamerounCorrespondence: Romaric Nzoumbou-Boko, Parasitology Laboratory, Pasteur Institute of Bangui, P.O. Box 923, Bangui, Central Africa Republic, Tel +236 75692448, Email romaric.nzoumbou-boko@pasteur-bangui.cfBackground: Malaria is a major public health problem in the Central African Republic (CAR). Data on malaria epidemiology are often derived from confirmed cases of symptomatic malaria using passive detection approaches, with very limited knowledge of the extent of subclinical and submicroscopic infections.Methods: A community-based cross-sectional study was conducted in Bangui, the capital of the CAR, to assess the prevalence of subclinical malaria parasitaemia. Proportions of positive tests for malaria parasites were determined by combining the results of antigen-based malaria rapid diagnostic test (mRDT), thick blood smear microscopy, and polymerase chain reaction (PCR).Results: A total of 638 participants (mean age, 26.44 years (range, [1– 75] years) with a sex ratio (M/F) of 1.22) were tested for malaria using all three detection methods. Proportions of positives were 32.45% by PCR, 27.59% by mRDT, and 23.51% by Giemsa-based thick blood smear microscopy, representing the burden of subclinical malaria. In addition, a 9.56% prevalence of submicroscopic infections was observed. Subclinical malaria was more common in individuals aged 15– 49 years, and microspatial heterogeneity in positivity was observed, with the majority of cases occurring in semi-urban areas by mRDT and microscopy, respectively. Approximately, 80% of microscopy-positive subjects had a low parasite density (< 1000 parasites/μL whole blood). Although P. falciparum was the most common species (98.55%), the transmission of P. ovale appears to be well-established in the area, occurring either as mono-infection (1.45%) or co-infection (1.93%) with P. falciparum.Conclusion: This study of community malaria in Bangui highlights the high burden of subclinical malaria in the community and provides essential baseline data to guide future research on malaria parasites in the CAR, particularly regarding the circulating parasite species. The high prevalence of community malaria demonstrates its persistence as a major public health challenge in the country, highlighting the need to intensify its ongoing control using new tools such as the upcoming malaria vaccine.Plain Language Summary: Malaria is widespread in the Central African Republic, with prevalence data based mainly on highly flawed medical records. Moreover, little is known about the extent of, and factors associated with subclinical Plasmodium infections, which are essential for guiding ongoing antimalarial interventions in the community. Subclinical infection is defined as an infection with no noticeable clinical symptoms.This study demonstrated that one out of three people living in Bangui is carrying malaria parasite without showing any symptoms. This high prevalence of low-density Plasmodium infections in the Bangui community, especially in 15– 49 age group, raises concerns about the persistence of malaria in the community and the opportunity for its elimination in CAR.The current findings underscore the need to intensify community-based interventions, including vaccination, against malaria, particularly in CAR and Bangui.Keywords: malaria, subclinical parasitaemia, Bangui, Central African Republic